2012
DOI: 10.1094/mpmi-03-12-0057-r
|View full text |Cite
|
Sign up to set email alerts
|

The P25 Pathogenicity Factor of Beet necrotic yellow vein virus Targets the Sugar Beet 26S Proteasome Involved in the Induction of a Hypersensitive Resistance Response via Interaction with an F-box Protein

Abstract: P25, a Beet necrotic yellow vein virus (BNYVV) pathogenicity factor, interacts with a sugar beet protein with high homology to Arabidopsis thaliana kelch repeat containing F-box family proteins (FBK) of unknown function in yeast. FBK are members of the Skp1-Cullin-F-box (SCF) complex that mediate protein degradation. Here, we confirm this sugar beet FBK-P25 interaction in vivo and in vitro and provide evidence for in planta interaction and similar subcellular distribution in Nicotiana tabacum leaf cells. P25 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 72 publications
0
29
0
Order By: Relevance
“…Yeast two-hybrid experiments evidenced the interaction of P25 with a number of candidate proteins involved in ubiquitination (Thiel and Varrelmann, 2009), in particular a protein containing an F-box domain and two Kelch repeats. The biological relevance of BNYVV P25 in terms of degradation remains unclear, but rather than P25 being a substrate of this host F-box protein, it has been proposed that P25 might inhibit the interaction between the SKP1 homolog ASK1 and the F-box protein, thereby altering proper target recognition and leading to cell necrosis in an as yet undefined manner (Thiel et al, 2012).…”
Section: Usurping Host E3 Ligases Through Recruitment Of F-box-contaimentioning
confidence: 99%
“…Yeast two-hybrid experiments evidenced the interaction of P25 with a number of candidate proteins involved in ubiquitination (Thiel and Varrelmann, 2009), in particular a protein containing an F-box domain and two Kelch repeats. The biological relevance of BNYVV P25 in terms of degradation remains unclear, but rather than P25 being a substrate of this host F-box protein, it has been proposed that P25 might inhibit the interaction between the SKP1 homolog ASK1 and the F-box protein, thereby altering proper target recognition and leading to cell necrosis in an as yet undefined manner (Thiel et al, 2012).…”
Section: Usurping Host E3 Ligases Through Recruitment Of F-box-contaimentioning
confidence: 99%
“…Several ubiquitin-interfering viral proteins interact directly with E3 family enzymes, in particular the cullin-based RING (really interesting new gene) finger-type ubiquitin ligase (CRL) SCF (Skp1, cullin, F-box) complex (4,5). The F-box protein is one of the four subunits of the SCF complex which mediates target recruitment for ubiquitination.…”
mentioning
confidence: 99%
“…We performed also high resolution melting analysis (HRM) after PCR for one of the products in order to identify potential Rz2-accompanying polymorphisms described earlier (Thiel et al 2012). As a result we found that one of the resistant cultivars repeatedly clustered with the susceptible-like profile as far as this sequence is concerned, displaying a heterozygote-like HRM profile (Fig.…”
Section: Rhizomania Resistance-segregating Markersmentioning
confidence: 76%